2020
DOI: 10.1111/jdv.16021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical severity measures and quality‐of‐life burden in patients with mycosis fungoides and Sézary syndrome: comparison of generic and dermatology‐specific instruments

Abstract: Background Given the severe symptom burden and chronic nature of mycosis fungoides (MF) and S ezary syndrome (SS), effective assessment of quality of life (QoL) is essential to guiding patient-centred care in this population. In this study, we aim to provide a comprehensive assessment of QoL in early-and advanced-stage MF/SS and to assess the correlation of traditional measures of clinical severity with QoL measures. Methods Between July 2017 and April 2019, outpatients at an academic medical centre with eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(73 citation statements)
references
References 35 publications
6
66
0
1
Order By: Relevance
“…Similar findings were recently observed in a larger cohort of patients with early stage MF although with different QoL instruments ( 5 ). In fact, for patients with higher stage MF (>IIA) overall a worse QoL was recently reported ( 2 , 5 ), indicating that disease stage per se does affect QoL more than area and extent of body involvement. A previous study reveals ( 1 ) that >93% of the surveyed MF patients worried about their disease being serious and >80% worried about dying.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar findings were recently observed in a larger cohort of patients with early stage MF although with different QoL instruments ( 5 ). In fact, for patients with higher stage MF (>IIA) overall a worse QoL was recently reported ( 2 , 5 ), indicating that disease stage per se does affect QoL more than area and extent of body involvement. A previous study reveals ( 1 ) that >93% of the surveyed MF patients worried about their disease being serious and >80% worried about dying.…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that patients with early stage MF are affected in QoL and psychological well-being irrespective of extent of disease (as measured by mSWAT). Similar findings were recently observed in a larger cohort of patients with early stage MF although with different QoL instruments (5). In fact, for patients with higher stage MF (>IIA) overall a worse QoL was recently reported (2,5), indicating that disease stage per se does affect QoL more than area and extent of body involvement.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Sampogna et al 20 found that impairment in global health status, emotional well‐being, fatigue, and insomnia were worse in patients with advanced stage disease. Other studies in the literature have also emphasized worse QoL scores for late‐stage MF patients and Sezary syndrome 15,22,29 . On the other hand, Holahan et al 30 did not detect such a relationship between stage of the disease and QoL, claiming that it may be due to the generally earlier stage of disease of their subjects.…”
Section: Discussionmentioning
confidence: 92%
“…In the literature similar studies have shown that 50% of the patients with a diagnosis of CTCL have limitations in their daily activities and social interactions. 13 Herbosa et al 22 also revealed reduced overall health status, with largest decrements in social functioning and usual role functioning. Although social activities and relations with family and friends are adversely affected from the disease; mood changes, pain or physical function scores were statistically similar to healthy controls in our study.…”
Section: Discussionmentioning
confidence: 93%